EVALUASI TRANSPARANSI DAN AKUNTABILITAS INVENTARISASI BMD PADA BADAN KEUANGAN PENDAPATAN DAN ASET DAERAH KABUPATEN BANGLI - Vikrama, Aditya Arya (CITIZEN CHARTER, 2017)
Predicate Fair With Exceptions to Bangli County Financial and Revenue Reports in 2015 refers to the record of many troubled assets. This happens due to lack of understanding of human resources related inventory procedures, so that in the year 2016 conducted a thorough evaluation of the inventory of Regional Property. The purpose of this study is to know the application of transparency and accountability in the evaluation of inventory of Regional Property in Bangli Regency. This research uses qualitative descriptive method as well as data collection techniques through field observation and in-depth interviews about the inventory of Regional Property in Bangli Regency. Problems regarding the evaluation of the inventory of Regional Assets in this study were dissected through the concept of Kristianten transparency as well as the accountability concepts of Jay M. Shafritz and E. Russel. Through an assessment of the indicators of accountability and transparency, it is seen that the implementation of inventory in the Asset Sector of Regional Income and Asset Finance Agency is accountable but not yet fully transparent as seen from some transparency indicators that are not achieved. The findings of this study are that there are some assets that are of unnatural value and are not recorded in accordance with the procedures of the Public Works Department and the Youth and Sports Education Department. Keywords: inventory, assets, transparency and accountability